2014
DOI: 10.1128/iai.01505-13
|View full text |Cite
|
Sign up to set email alerts
|

ALOX12 in Human Toxoplasmosis

Abstract: jALOX12 is a gene encoding arachidonate 12-lipoxygenase (12-LOX), a member of a nonheme lipoxygenase family of dioxygenases. ALOX12 catalyzes the addition of oxygen to arachidonic acid, producing 12-hydroperoxyeicosatetraenoic acid (12-HPETE), which can be reduced to the eicosanoid 12-HETE (12-hydroxyeicosatetraenoic acid). 12-HETE acts in diverse cellular processes, including catecholamine synthesis, vasoconstriction, neuronal function, and inflammation. Consistent with effects on these fundamental mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 19 publications
0
38
1
Order By: Relevance
“…The human ALOX12 gene has susceptibility alleles for human congenital toxoplasmosis and RNAi-mediated expression knockdown of this gene attenuated progression of T. gondii infection [398]. These data implicate ALOX12 in host defense against T. gondii but the underlying molecular mechanisms remain unclear.…”
Section: Lipoxygenase Isoforms In Infectious Diseasesmentioning
confidence: 99%
“…The human ALOX12 gene has susceptibility alleles for human congenital toxoplasmosis and RNAi-mediated expression knockdown of this gene attenuated progression of T. gondii infection [398]. These data implicate ALOX12 in host defense against T. gondii but the underlying molecular mechanisms remain unclear.…”
Section: Lipoxygenase Isoforms In Infectious Diseasesmentioning
confidence: 99%
“…The infection is usually asymptomatic and is characterized by the formation of inactive cysts with bradyzoites located in the tissues. However, in individuals with reduced immunity or congenital infection, toxoplasmosis may develop into a very severe form (24).…”
Section: Relationship Between T Gondii and Modulation Of Neurotransmmentioning
confidence: 99%
“…Thus, it has been demonstrated that a critical role in human congenital T. gondii infection is played by the ALOX12 gene, which encodes arachidonate 5-lipoxygenase enzyme, which is involved in fatty acid metabolism and has been related to schizophrenia, at least in a Korean population [190,191]. HLA-related genes such as SGK1 on chromosome 6, which plays a role in regulating different brain functions [192] and mediates the effects of cortisol on hippocampal neurogenesis [193], have a modulating effect on some infectious agents, including T. gondii, consistent with the proposition that parasitization may modify the risk of schizophrenia [187].…”
Section: Studies On Gene-infection Interactionmentioning
confidence: 99%